Income Shocks or Insurance - What Determines Consumption Inequality? - Johannes Ludwig (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Contrary to the implications of economic theory, consumption inequality in the US did not react to the increases in income inequality during the last three decades. This paper investigates if a change in the type of income inequality - from permanent to transitory - or a change in the ability to insure income shocks is responsible for this. A measure of household consumption is imputed into the Panel Study of Income Dynamics to create panel data on income and consumption for the period 1980-2010. The minimum distance investigation of covariance relationships shows that both explanations work together: the share of transitory shocks increases over time, but the capability to insure permanent and transitory shocks to income also improves. Together, these phenomena can explain the lack of an increase in consumption inequality. – – Entgegen der Vorhersage ökonomischer Theorie reagiert die Ungleichheit des Haushaltskonsums in den USA nicht auf den Anstieg der Einkommensungleichheit der letzten drei Jahrzehnte. Dieses Papier untersucht, ob eine Veränderung der Art der Einkommensungleichheit - von permanenter zu transitorischer - dafür verantwortlich ist oder eine Veränderungen in der Fähigkeit der Haushalte, Einkommensschocks abzufedern. Ein Maß für Haushaltskonsum wird in die Daten der Panel Study of Income Dynamics imputiert, um einen Paneldatensatz für die Jahre 1980-2010 zu erstellen, der Einkommen und Konsum beinhaltet. Die Minimum Distance-Analyse der Kovarianzstrukturen zeigt, dass beide Erklärungsansätze gemeinsam wirken: Der Anteil transitorischer Schocks steigt im Zeitverlauf, aber die Fähigkeit, permanente und transitorische Einkommensschocks abzufedern, verbessert sich ebenfalls. Zusammen können diese Phänomene erklären, warum die Ungleichheit des Haushaltskonsums nicht ansteigt.
Keywords: D12; D31; E21; 330; consumption inequality; income inequality; consumption insurance